Comparison of Outcome of Ingrowing Toenail Surgery—Simple Nail Removal V/S Wedge Resection - Ashraf, Junaid; Hussain, Syed Mukarram; Gilani, Syed Talha Hassan; Ahmed, Rizwan; Zia, Shakeel Ahmed; Minhas, Sultan Ahmed (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare outcome of ingrowing toenail surgery—simple nail removal v/s wedge resection. Study Design: Quasi-experimental study. Place and Duration of Study: Combined Military Hospital, Rawalpindi, Pakistan, from Mar 2022 to Feb 2023. Methodology: A total of 100 patients were enrolled and randomly divided into two equal groups. Group A cases were treated with simple nail removal whereas Group B was allotted Wedge resection. Both of these techniques were compared for operative time, recurrence of ingrowing toenail and post operative infection. Results: The mean age of the patients in Group A was 37.86±9.33 years and in Group B, it was 41.08±7.59 years (p-value=0.061), while gender distribution showed that males numbered 29(58%) in Group A and 31(62%) in Group B whereas, females comprised 21(42%) in Group A and 19(38%) in Group B, (p-value=0.68). Mean operative time in Group A was 10.68±2.23 minutes and in Group B it was 10.30±2.67 minutes while recurrence was recorded as 2(4%) in Group A and 3(6%) in Group B. We found post operative infection in 1(2%) patient in both groups with p-value>0.999. Conclusion: We found no significant difference in both techniques regarding recurrence, post operative infection, and operative time. However, simple nail removal is well tolerated, and does not present any technical challenges; hence, it ought to be regarded as an alternative to other techniques of treatment.